A Novel SNPs of KISS1 Gene Strongly Associated with Litter Size in Indonesian Goat Breeds - A. Febriana; S. Sutopo; E. Kurnianto; W. Widiyanto (Faculty of Animal Science, Bogor Agricultural University, 2022)
Kisspeptin is a protein encoded by the KISS1 gene which behaves as a key role by stimulating gonadotropin releasing hormone (GnRH) neuron activity directly in the reproductive axis. The objective of the present study was to determine the genetic diversity within intron 1 of KISS1 gene and to verify their association with fecundity traits which can be devoted as a marker assisted selection (MAS) for breeding selection. This study was established on three Indonesian native goat populations (Kacang, Kejobong, and Senduro). The PCR products were then sequenced in both directions. The DNA sequencing alignment resulted fifteen variants (one indel and fourteen SNPs), with SNP1, SNP2, SNP3, and SNP9 being novel single nucleotide polymorphisms (SNPs) of KISS1 gene intron 1. Genotype, haplotype, and parity were significantly associated with litter size. SNP8, SNP9, and SNP10 were correlated with overall means of litter size (LS) and LS at the first and the third parities (p<0.05). Additionally, novel SNP9 were in remarkably strong linkage disequilibrium with SNP8 and SNP10 (D’=1.00; r≥0.58; χ2≥13.38), and allele A had putative binding sites for the NFIC which plays an important role in activating the expression of KISS1 gene. The H2 haplotype (CATAGCGCAACGCT) was found to have the highest litter size (p<0.0001). CC genotype at SNP8, AA genotype at novel SNP9, GA genotype at SNP10, and H2 haplotype were the excellent genotypes and haplotype that associated with the superior LS (p<0.05). Therefore, this result led to presume that these three SNPs and H2 haplotype can be acknowledged as prominent genetic markers for goat- breeding selection.